Abortion Legalization and Social Representations of Feminism in Argentina - Alonso, Daniela Rocío (2021)
Over the last few years, the Argentinian feminist movement has experienced remarkable growth in its volume, scope, and public recognition. Positioned within the massive mobilization for the legalization of voluntary termination of pregnancy (VTP), we are interested in addressing feminism as a social movement. Thus, we propose an analysis of social representations (SRs) of feminism as a means of studying collective identity. We also describe the role of attitudes towards VTP legalization as a cleavage that configures two opposing representations of feminism. We took a sample of 772 people from 16 to 81 years of age (M = 37.8, SD = 17.1). Applying a word association technique, we gathered information about participants’ SRs of feminism, together with information about their attitudes towards VTP legalization, political ideology, political interest, the personal relevance of religion, and participation in social and political actions and/or organizations regarding gender and/or sexual diversity matters. Our results evidenced a generally positive representation of feminism, but one that is conditioned by attitudes towards abortion legalization: that is, people who were in favour of VTP legalization expressed positive associations, mainly referring to feminism as a social movement, emphasizing the political dimension. In contrast, people who were against VTP legalization were more likely to hold a mainly negative representation of feminism, exemplified by representations of specific women who act motivated by hatred, resentment, and contempt towards men, and who express an authoritarian seek for a dominant position in society. We discuss the implications of these results in terms of collective identity.